Câu 2:
a: ĐKXĐ: \(x\notin\left\{2;-2\right\}\)
\(A=\dfrac{x}{2x-4}-\dfrac{3x-2}{x^2-4}\)
\(=\dfrac{x}{2\left(x-2\right)}-\dfrac{3x-2}{\left(x-2\right)\left(x+2\right)}\)
\(=\dfrac{x\left(x+2\right)-2\left(3x-2\right)}{2\left(x-2\right)\left(x+2\right)}\)
\(=\dfrac{x^2+2x-6x+4}{2\left(x-2\right)\left(x+2\right)}=\dfrac{x^2-4x+4}{2\left(x-2\right)\left(x+2\right)}\)
\(=\dfrac{\left(x-2\right)^2}{2\left(x-2\right)\left(x+2\right)}=\dfrac{x-2}{2\left(x+2\right)}\)
b: Để A=0 thì \(\dfrac{x-2}{2\left(x+2\right)}=0\)
=>x-2=0
=>x=2(loại)